Pediatric migraine equivalents - P. V. Zhmylyova; G. R. Tabeeva; A. V. Sergeev (Неврология, нейропсихиатрия, психосоматика, 2021)
Migraine is a common disease in pediatric practice. Its manifestations are extremely diverse in children. Pediatric migraine equivalents are a group of different disorders that are closely related to migraine and are more common in children long before the manifestation of migraine headache. Their verification presents significant difficulties in clinical practice, and this often predetermines the use of inadequate management strategies for these patients. Meanwhile, the diagnosis of and approaches to treating pediatric migraine equivalents have their own characteristics, the knowledge of which can significantly determine quality of life in patients. The paper considers modern ideas about pediatric periodic syndromes and data on their relationship to migraine and discusses the issues of their diagnosis and treatment.